Least Weight Design of Truss Structures By Sequential Linear Programming - Mahmud Sami Döven; Burak Kaymak; Mehmet Tevfik Bayer (Pamukkale University Journal of Engineering Sciences, 2011)
In this study, truss structures which are under several loading conditions and subject to displacement, stress and member cross-sectional area constraints, are examined and a new optimization model is put forward in order to minimize the weight by using Sequential Linear Programming technique. A computer code is developed in order to solve this model. Using this computer code some example problems taken from literature are solved and it is observed that solutions are similar to each other.